“Ho Imparato um po’... um po’ a pensare in inglese”: potentialities of literature in Brazilian and Italian public schools, in the light of sociocultural historical theory - Seerig, Elisa (Universidade do Vale do Rio dos Sinos, 2024)
The literary text has humanising potential, it is understood as an "emotional calibrator" and, for this reason, everyone should be permitted its access. In the study of English in basic education, however, various circumstances mean that its approach is neglected or only focussed on structural issues of the language. Among the many reasons for this are the low weekly workload, teachers' excessive number of classes, educational regulations that do not include literary texts, and the diverse proficiency levels of students in the same group. In addition, there is the belief that one must have a certain level of language acquisition to be able to appreciate literature in English. Given the importance of reading and writing literature for not only linguistic but also subjective development, this thesis aims to encourage the development of critical literacy in English in these spheres. To this end, this study sought to identify the potentialities of a brief teaching proposal, consisting of two 50-minute lessons, focused on reading, discussing, and writing a literary text (poem/song) in English, developed and analysed in the light of Vygotsky's Sociocultural Historical Theory. These lessons took place in two contexts, in the first year of Technical Secondary Education: in Brazil, in 2021, remotely due to the Covid-19 pandemic, and in Italy, in person, in 2023. Data generated includes the lessons given, the questionnaires answered by the students about their learning of English and their contact with literature in the language, as well as interviews conducted with volunteer students after the lessons, being two from Brazil and seven from Italy. Based on Sociocultural Historical Theory concepts, and using Content Analysis to organize the data, the results attest: i) the importance of proposing varied activities that provide students with the vocabulary needed to understand the literary text, at the different proficiency levels of the class (thus potentializing the different Zones of Proximal Development) ii) the relevance of discussing the text in groups to stimulate critical literary literacy; and iii) the positive impacts of providing poetry writing as a subjective and meaningful way of acquiring the new language, generating, in this set of activities, motivation to continue learning. It also sheds light on the importance of continuous teacher education, so that they master strategies and feel motivated to apply them in their classrooms, even with little time and few resources available. Academically speaking, this thesis also contributes to the necessary approximation of the traditionally separate of Linguistics and Literature in the field of Letters.

Il testo letterario ha un potenziale umanizzante, è inteso come un "calibratore emozionale" e, per questo motivo, a tutti dovrebbe essere consentito il suo accesso. Nell'ambito dello studio dell'inglese nell'istruzione di base, tuttavia, diverse circostanze fanno sì che il suo approccio venga trascurato o si concentri solo su questioni strutturali della lingua. Tra le molte ragioni vi sono il basso carico di lavoro settimanale, l'eccessivo numero di lezioni degli insegnanti, i regolamenti didattici che non includono testi letterari e i diversi livelli di competenza degli studenti nello stesso gruppo. Inoltre, c'è la convinzione che si debba avere un certo livello di acquisizione linguistica per poter apprezzare la letteratura in inglese. Data l'importanza della lettura e della scrittura della letteratura per lo sviluppo non solo linguistico ma anche soggettivo, questa tesi si propone di incoraggiare lo sviluppo di una literacy critica in inglese in questi ambiti. A tal fine, questo studio ha cercato di individuare le potenzialità di una breve proposta didattica, consistente di due lezioni di 50 minuti, incentrate sulla lettura, la discussione e la scrittura di un testo letterario (poesia/canzone) in inglese, sviluppato e discusso alla luce della Teoria Socioculturale Storica di Vygotsky. Queste lezioni si sono svolte in due contesti, nel primo anno dell'istruzione superiore tecnica: in Brasile, nel 2021, a distanza a causa della pandemia di Covid-19, e in Italia, di persona, nel 2023. I dati generati comprendono le lezioni tenute, i questionari compilati dagli studenti sull'apprendimento dell'inglese e sul loro contatto con la letteratura in tale lingua, nonché le interviste condotte con gli studenti volontari dopo le lezioni, due dal Brasile e sette dall'Italia. Sulla base dei concetti della Teoria Socioculturale Storica e utilizzando l'Analisi del Contenuto per organizzare i dati, i risultati attestano: i) l'importanza di proporre attività diversificate che forniscano agli studenti il vocabolario necessario per comprendere il testo letterario, ai diversi livelli di competenza della classe (potenziando così le diverse Zone di Sviluppo Prossimale); ii) l'importanza di discutere il testo in gruppo per stimolare l'alfabetizzazione letteraria critica; e iii) l'impatto positivo di fornire la scrittura di poesie come un modo soggettivo e significativo di acquisire la nuova lingua, generando, in questa serie di attività, la motivazione a continuare l'apprendimento. Inoltre, fa luce sull'importanza della formazione continua degli insegnanti, in modo che conoscano le strategie e si sentano motivati ad applicarle nelle loro classi, anche con poco tempo e poche risorse a disposizione. Dal punto di vista accademico, questa tesi contribuisce anche al necessario avvicinamento della linguistica e della letteratura, tradizionalmente separate nel campo delle Lettere.
Keywords: Ensino de inglês no Ensino Médio; Literatura em língua inglesa; Letramento literário; Escrita criativa em língua inglesa; Teoria Sócio-Histórico-Cultural; Perezhivanie; Secondary school English teaching; English language literature; Literary literacy; Creative writing in English; Sociocultural-Historical Theory; Insegnamento dell'inglese nella scuola superiore; Letteratura inglese; Literacy letteraria; Scrittura creativa in inglese; Teoria Socioculturale Storica; ACCNPQ::Lingüística, Letras e Artes::Lingüística